(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study explores the pivotal role of mass media in promoting health awareness campaigns and influencing public health behavior across global and national contexts before 2018. Utilizing a mixed-method research approach, the analysis integrates quantitative data from large-scale health campaigns and qualitative insights from existing literature. Findings reveal that multi-channel communication strategies—combining television, radio, print, and community media—significantly enhance awareness levels and foster behavioral change. Campaigns such as India’s Pulse Polio and the United States’ Truth Initiative demonstrated how consistent, credible, and emotionally persuasive messages can mobilize communities toward preventive action. Qualitative themes including message credibility, cultural adaptation, and repetition emerged as core determinants of effectiveness. The study concludes that health communication through mass media not only informs but also empowers individuals to make informed health decisions, contributing to sustainable improvements in public well-being. By bridging the gap between policymakers and the public, mass media remains an indispensable tool for achieving equitable health literacy and long-term societal health transformation.